A New Approach to Assess Early Progressive Loss Across Multiple Visual Channels In the Natural History of Glaucoma. Issue 6 (June 2016) - Mateus, Catarina; Raimundo, Miguel; Oliveiros, Bárbara; Faria, Pedro; Reis, Aldina; Castelo-Branco, Miguel
Abstract : Purpose: We aimed to evaluate the ability of new psychophysical discrimination tests, based on readily available hardware, to probe motion, achromatic, and chromatic contrast sensitivity, across the natural history of glaucoma. We assessed the sensitivity of these tests to detect functional damage at ocular hypertension stage, using receiver operating characteristic analysis. We also explored whether eccentricity-related patterns of damage change with disease progression. Patients and Methods: We studied a cohort of 43 participants, who were divided between different groups: ocular hypertension (n=16 eyes), glaucoma suspects (n=15), and primary open-angle glaucoma (n=12). These patients were compared with an age-matched control group (n=15 eyes). We tested distinct subsets of retinal ganglion cell populations using 3 novel 2-alternative forced choice psychophysical discrimination tests (independent variables: motion, achromatic, and chromatic L, M, and S-cone contrasts) between 2 separated peripheral, small moving single dots at 4 distinct meridians. Notably these tests were implemented in relatively standard hardware. Results: All tests showed significant correlation with disease progression (mean ρ±SD=0.708±0.075; P <0.0001) and had sufficient power to discriminate glaucoma subgroups. Most tests using this design had large sensitivity (above 90% for 80% specificity) to detect functional damage at the ocular hypertensive stage. Disease-related eccentricity patterns of damage were also found, matching the expected pattern of progression. Conclusions: Our new psychophysical discrimination tests are capable of probing disease progression and to detect functional damage at ocular hypertension stage. It is therefore possible to customize psychophysical test software to detect early changes and monitor disease progression, including progressive loss of functional reserve, using relatively simple hardware.